An Integrative Model of Digital Financial Inclusion in Indonesia: The Role of Financial Literacy, Fintech Adoption, and The Use of Open Finance - Yasrizal, Yasrizal; Mahdani, Said; Mahrizal, Mahrizal; Arimi, Sailal (Teunuleh Publisher, 2025)
Digital financial inclusion has emerged as a strategic pathway to ensure that all segments of society—including those in remote areas—can access financial services fairly and easily. Despite the rapid growth of financial technology and increasing internet penetration, significant barriers still hinder the optimal use of digital financial services. This study develops an integrative model based on a systematic literature review of reputable international publications over the past decade, aiming to explore how financial literacy, attitudes toward technology, risk perception, and trust shape individuals’ decisions to adopt fintech services. The findings reveal that financial literacy not only drives fintech adoption but also enhances the quality of digital financial service usage. Meanwhile, risk perception remains a major barrier, whereas trust and positive attitudes toward technology act as key enablers. Fintech adoption serves as a crucial bridge toward broader financial inclusion, with open finance further strengthening this relationship by enabling more personalized, efficient, and integrated financial services. The study recommends strengthening digital financial literacy programs, enhancing consumer protection frameworks, and accelerating the development of open finance regulations as critical steps toward a safer, fairer, and more inclusive digital financial ecosystem in Indonesia.